2023
DOI: 10.3389/fonc.2023.1083053
|View full text |Cite
|
Sign up to set email alerts
|

High-risk multiple myeloma predicted by circulating plasma cells and its genetic characteristics

Abstract: IntroductionCirculating plasma cells (CPC) have been reported to be one of the indicators of high-risk multiple myeloma (MM), yet the prognostic significance of CPC in Chinese population and the genetic mechanisms underlying CPC formation have not been fully elucidated.MethodsPatients with newly diagnosed MM were included in this study. We used multi-parameter flow cytometry (MFC) for CPC quantification and next-generation sequencing (NGS) technology for mutational landscape mapping to identify the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…However, this test is not routinely available outside of select US institutions. Given the increasing sensitivity of peripheral blood flow cytometry assays, multiple groups have also demonstrated that circulating plasma cells are a predictor of early relapse whether detected at diagnosis or during stem cell collection ( 37 , 114 116 ). Advanced imaging modalities such as whole-body diffusion-weighted magnetic resonance imaging may play a role in FHRMM prognostication as well, given that persistence of focal lesions after induction may be indicative of a worsened prognosis ( 117 , 118 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this test is not routinely available outside of select US institutions. Given the increasing sensitivity of peripheral blood flow cytometry assays, multiple groups have also demonstrated that circulating plasma cells are a predictor of early relapse whether detected at diagnosis or during stem cell collection ( 37 , 114 116 ). Advanced imaging modalities such as whole-body diffusion-weighted magnetic resonance imaging may play a role in FHRMM prognostication as well, given that persistence of focal lesions after induction may be indicative of a worsened prognosis ( 117 , 118 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this test is not routinely available outside of select US institutions. Given the increasing of peripheral blood flow cytometry assays, multiple groups have also demonstrated that circulating plasma cells are a predictor of early relapse whether detected at diagnosis or during stem cell collection (37,(114)(115)(116).…”
Section: Discussionmentioning
confidence: 99%